Profil Profil Kemandirian Belajar Peserta Didik Kelas II SDN Gajahmungkur 04: Kemandirian Belajar - Kiki Suci Menkasari; Veryliana Purnamasari; Paryuni (UNIB Press, 2024)
This research aims to explain the learning independence profile of second grade students at SDN Gajahmungkur 04. The research subjects were students of class two at SDN Gajahmungkur 04, totaling 16 children. The approach used in this research is qualitative with descriptive research type. Data collection techniques through observation, interviews, questionnaires and documentation. The questionnaire method calculation uses a Likert scale with the formula P = F/N x 100% and is categorized into a rating scale. Based on the research results, it can be concluded that the learning independence of class II students at SDN Gajahmungkur 04 is developing well and is very interactive so that the interaction of the teaching and learning process can take place as expected. This can be seen from the average results of the learning independence questionnaire of 77.23% with good criteria.